Assessment Of Knowledge, Attitude and Practice About Hepatitis B Among Clinicians & Medical Students: A Cross Sectional Study - Baig, Vaseem Naheed; Gupta, Pankaj Kumar; Sharma, Arvind Kumar; Swarnkar, Madhusudan (National Journal of Community Medicine, 2015)
Background: Hepatitis B (HB) is a serious global public health problem that causes chronic liver disease and accelerates high risk of death from cirrhosis of the liver and liver cancer. Present study aims to evaluate Knowledge, Attitude and Practice (KAP) towards HB among Clinicians & students of Jhalawar Medical College, Ra- jasthan. Methods: A cross sectional, descriptive study was undertaken. 500 Clinicians & Medical students were approached for the study. KAP towards HB was assessed by using a pre validated questionnaire. Descriptive statistics were used for elaborating participants’ demo- graphic characteristics while Pearson’s correlation was used to identify association between the study variables. Results: Out of 500 distributed questionnaires, 354 were returned with a response rate of 70.80%. Majority of them were Medical stu- dents (60.2%) & rest were Clinicians. Mean scores for knowledge, attitude and practice were 15.66 ± 1.9, 7.17 ± 1.15 and 6.8 ± 1.13 re- spectively. Significant and positive linear correlations between des- ignation vs. knowledge (r = 49.18, p < 0.00); vaccination status vs. knowledge (r = 28.88, p < 0.001); duration of experience vs. knowledge (r = 23.51, p < 0.001) and attitude vs. vaccination status (r =3 0.14, p < 0.05) were observed. Conclusion: Clinicians & Medical students reflected fairly moder- ate level of KAP regarding HB infection and vaccination with im- portant gaps.